Molecular Genetic Analysis of the alpha-latrotoxin Receptor Latrophilin in the Nematode Caenorhabditis elegans. - Mee, Christopher (2002)
The venom of the black widow spider (BWSV) uniquely contains a family of high molecular weight proteins that cause uncontrolled vesicle release in synapses. Two membrane receptors for BWSV have been identified, one of these being latrophilin/CIRL (LPH), a member of the G-protein coupled receptor superfamily of cell-signalling receptors and the other being neurexin. In mammals, LPH and neurexin have been shown to bind BWSV, but their function is unclear. We established C.elegans as a model system for studying the effects of BWSV by microinjection of venom into wild-type (N2) C.elegans, which showed that the venom had an acute lethal effect over a million-fold range of concentrations. BWSV treated with SDS (0.1%) or heat before injection reduced the kill rate in N2 C.elegans to zero, this suggests that the active component of the venom is a protein. FPLC of BWSV demonstrated that the active component of BWSV toxic to C.elegans resembles epsilon- latroinsectotoxin. Identification of a homologue of the latrophilin gene in C.elegans, BO457.1, induced a functional knockout of the latrophilin gene by RNA interference (RNAi). The knockout was examined for a change in phenotype, which occurred in RNAi treated worms, compared to N2, and was extensively characterised. LPH knockout C.elegans were completely resistant to the lethal effects of BWSV over the same concentration range as that used in the N2 worms, whereas RNAi of CYP37A1, BO286.2 and neurexin 1alpha homologue has no effect on BWSV toxicity. We have shown that a C.elegans latrophilin homologue mediates the toxic effects of black widow spider venom in the nematode and identified a high molecular weight latrotoxin that kills C.elegans. Additionally, the data provide evidence for an important role of LPH in nerve cell function.